The Bronze and Iron Age site of Kamaris (according to the materials at the History Museum of Armenia) - Hovsepyan, Sona (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
The main purpose of the article is to reveal and to put into circulation the material from the excavations of the site of Kamaris, kept in the archaeological funds of the History Museum of Armenia (hereinafter HMA), which unfortunately for many years had been left out of the study area being closed in the HMA funds, inaccessible for study due to the lack of written information by research expeditions. Brief information about the site might be obtained through mentioning of this name in various publications and the descriptions in registries of the HMA, which only help to find out about the expeditions that excavated the site and the dates. It includes a diverse collection of the Early Bronze Age culture of Armenia, further expanding the comparative knowledge on this region.